Outcomes of external dacryocystorhinostomy and endoscopic endonasal dacryocystorhinostomy in the management of nasolacrimal duct obstruction - Duwal, S; Saiju, R (Nepalese Journal of Ophthalmology, 2015)
Introduction: Dacryocystorhinostomy (DCR) is the treatment of choice for nasolacrimal duct obstruction. Although external DCR is regarded as the gold standard, endoscopic DCR is evolving as an equally-effective alternative. Objectives To compare the success rate of treating nasolacrimal duct obstruction by endoscopic endonasal method compared to the conventional DCR surgery.Materials and methods This prospective, comparative, non-randomised study was conducted in 2009 - 2010. Thirty consecutive patients undergoing endoscopic endonasal DCR (Group 1) and 30 consecutive patients undergoing external DCR (Group 2) between July 2009 and September 2010 at the oculoplasty unit of the Tilganga institute of ophthalmology were included in this study. A patent lacrimal passage on syringing and symptomatic improvement at six months after surgery was de¿ned as a successful outcome. The intraoperative and postoperative complications were also compared. Results Our study included 31 eyes of 30 patients in Group 1 and 34 eyes of 30 patients in Group 2. The success rate for endoscopic endonasal dacryocystorhinostomy was 90.3 % (95 % con¿dence interval 80 - 100) and external dacryocystorhinostomy was 94.1 % (95 % con¿dence interval 80 - 100). The difference of surgical success among the two methods was not statistically significant (p = 0.7). The rate of intra-operative and post-operative complications was similar in the two methods (p = 0.5). Conclusion: The short term outcomes and complication rates of endoscopic endonasal dacryocystorhinostomy and external dacryocystorhinostomy were similar.